Analysing and forecasting the underemployment trend in Malaysia - Islam, Mohd Aminul; Syifa binti, Kamarudin (Malwa International Journals Publication, 2017)
In this paper we aim to examine and forecast the underemployment trend in Malaysia. We primarily focus on two measurements of underemployment which are time-related and skill-related underemployment for a period of ten years starting from 2005 to 2015. To forecast the number of time-related and skill-related underemployment for 2016 we use exponential smoothing forecast method. The data and other information related to underemployment in Malaysia are collected from Department of Statistics, Malaysia. The study found that although the proportion of time-related underemployment over employment is relatively stable during the ten years period, the number of skill-related underemployment is increasing by years. Females are mostly affected by both time-related and skill-related underemployment.